Istota równowagi na rynkach ubezpieczeniowych - Ostasiewicz, Stanisława (The essence of equilibrium on insurance markets, 2005)
The main goal o f this paper is to analyze the conditions for the existence o f equilibrium on the com petitive insurance markets. These conditions are analyzed for two elementary markets. One o f them consist o f agents facing the same risk and having the same utility functions. The second kind o f analyzed markets consists o f two groups o f individuals called low-risks and high-risks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 37-44